Respuesta :

Answer:

a) [tex]\frac{f(x+h)-f(x)}{h}=\frac{-5}{(x+h-3)(x-3)}[/tex]

b) [tex]\frac{f(h-6)-f(-6)}{h}=\frac{5}{9h-81}[/tex]

Step-by-step explanation:

The given function is [tex]f(x)=\frac{5}{x-3}[/tex]

[tex]f(x+h)=\frac{5}{x+h-3}[/tex]

[tex]\frac{f(x+h)-f(x)}{h}=\frac{\frac{5}{x+h-3}-\frac{5}{x-3}}{h}[/tex]

[tex]\frac{f(x+h)-f(x)}{h}=\frac{5(x-3)-5(x+h-3)}{h(x+h-3)(x-3)}[/tex]

[tex]\frac{f(x+h)-f(x)}{h}=\frac{5x-15-5x-5h+15}{h(x+h-3)(x-3)}[/tex]

[tex]\frac{f(x+h)-f(x)}{h}=\frac{-5h}{h(x+h-3)(x-3)}[/tex]

[tex]\frac{f(x+h)-f(x)}{h}=\frac{-5}{(x+h-3)(x-3)}[/tex]

When x=-6

[tex]\frac{f(h-6)-f(-6)}{h}=\frac{-5}{(-6+h-3)(-6-3)}[/tex]

[tex]\frac{f(h-6)-f(-6)}{h}=\frac{-5}{(h-9)(-9)}[/tex]

[tex]\frac{f(h-6)-f(-6)}{h}=\frac{5}{9h-81}[/tex]

ACCESS MORE